Architecture now 4! - Jodidio, Philip, 1954- (Köln : Taschen, 2006)
Architects at the cutting edgeArchitecture Now! Volume 3 was the winner of the prestigious Saint-Etienne Prize for the Best Architecture and Design Book of 2004. Volume 4 proves that the best keeps getting better, with new names from all over the world and the most exciting and unique buildings and designs. As always, easy-to-navigate illustrated A-Z entries include current and recent projects, biographies, contact information, and website addresses. Here are just a few of the projects that are featured in the new book: A shelter for the needy made out of sandbags Nomadic Museum made by Shigeru Ban out of shipping containers A tree house in Germany New Museums that have been built by Gehry, Mansilla and Tuñón, Richard Meier or Herzog & de Meuron The BMW Central Building in Leipzig by Zaha Hadid Klein Dytham's amazing Wedding Chapel in Japan Design hotels in Berlin, São Paulo, and Cerro Paranal, Chile The new masterpiece by Rem Koolhaas/OMA - the Central Library in Seattle Private houses in Mexico City, São Paulo, Corsica, and Great Mackerel Beach, Australia Mix Las Vegas by Patrick Jouin A tower that will grow like a tree in New York With-it architects like David Adjaye, Caramel, Graftlab, Jakob +MacFarlane, Asymptote or Lewis Tsurumaki Lewis Artists who take on architectural space like Anselm Kiefer, Frank Stella and Bill Viola, or architects who are interested in art, like Peter Eisenman.
Keywords: Architectuur -- Geschiedenis -- 20ste eeuw; Architectuur -- 1990-.